Factors Associated with Smoking in Pregnancy (Revista Latino-Americana de Enfermagem, 2010)
The aim of this cross-sectional study was to identify factors related to smoking during pregnancy. The sample included 267 puerperae hospitalized in the maternity unit of a university hospital in Porto Alegre/RS. The data were collected through a self-applied instrument and statistically analyzed. The majority of the puerperae (51.3%) were between 18 and 25 years old, 55.4% were nonsmokers, 25.5% were smokers, 19.1% had recently ceased smoking (in abstinence). The nonsmokers had more consultations than the smokers and the abstinent smokers (p=0.025). The number of women who had more than one child was higher among smokers than among nonsmokers and abstinent smokers (p=0.002). Women were more likely to stop smoking before pregnancy when they had a partner who was a nonsmoker (p=0.007). Several factors influence smoking and smoking cessation and these are important in prenatal interventions aimed at pregnant women and their partners.